Роль персонажа в предвыборном дискурсе - Марьянчик, Виктория (Studia Rossica Posnaniensia, 2015)
This article analyzes a universal axiological model of a media-related and political text and presents the concept of a role, which is one element of this structure. The author reviews the conceptions of a role that are implemented in psychological, literary and journalistic areas and proposes a new interpretation of the role of a media and politics person which can be represented as set of functions that this person carries out in discourse. The functional aspect of a ‘role’ is analyzed based on the example of preelection discourse, including a participant in the discourse. This article offers a typology of roles which serve a utilitarian, communicative, ethical, verbal, metaphorical and mythological function.